21st Century learning transformation for special needs students: Redesigning educational spaces in Special Education Schools - Zainon, Othman; Zakaria, Siti Radiaton Adawiyah; Mohd Yusoff, Nurul Syakima; Md. Yunus, Norhidayah; Zainudin, Ainur Zaireen; Adi Maimun, Nurul Hana (Jurnal Pendidikan Bitara UPSI, 2025)
The transformation of 21st century education emphasizes inclusivity, innovation, and adaptability to meet the diverse needs of students, including those with special needs. This study explores the impact of redesigning educational spaces in special education schools to enhance learning outcomes for students with unique learning requirements. By integrating principles of universal design, sensory-friendly environments, and collaborative spaces, the research identifies key elements that contribute to creating supportive and stimulating learning environments. According to the Malaysian Education Act 1996, integrated education programs with conducive infrastructure facilities and learning spaces are necessary for students with special needs in line with SDG4 of Education Quality and SSDG9 of UNESCO Infrastructure. Four sub-projects have been planned involving infrastructure, conducive learning spaces, quail farming and economic generation of the Herb Park. This project is implemented with community and industry network certificates. All projects have been implemented within 12 months involving surveys, knowledge transfer, preparation of 21st century learning spaces and communal work. The results of the project effectiveness evaluation showed that the participants had benefited from this project through the addition of knowledge on herb crops, quail farming, 21st century learning and entrepreneurship. On average, 65% of students strongly agree and 32% of students agree that this program is indispensable to them. This shows that programs like this can help students improve their learning performance in the classroom. Furthermore, 68% of students strongly agreed and 19% of students agreed that they really had knowledge of learning in the 21st century classroom. The study employs a quantitative analysis of student engagement. Findings reveal that thoughtfully designed learning spaces not only improve accessibility but also foster emotional well-being, creativity, and active participation among special needs students.